Personality-oriented Technology of Training a Future Teacher in the University Educational Process - R. M. Asadullin; O. V. Frolov (Высшее образование в России)
The article presents a new look at the content of personality-oriented pedagogical education, taking into account the patterns of professional development of future teachers, the peculiarities of structuring the content of education and the technologies used to form the personality of a future teacher as a subject of professional pedagogical activities. The authors believe that university pedagogy requires a different methodology for organizing pedagogical education, the purpose of which is to introduce future teachers to the essence of professional activities aimed at professional development. In the context of personality-oriented pedagogical education, the behavioral growth of future teachers associated with the assimilation of knowledge and methods of pedagogical activities is reflected in the student’s mind as a special goal and subject of educational and professional activities. As a result, professional development appears as the construction of oneself in the area of the university educational process.